2003
DOI: 10.1182/blood-2003-01-0189
|View full text |Cite
|
Sign up to set email alerts
|

Molecular remission after myeloablative allogeneic stem cell transplantation predicts a better relapse-free survival in patients with multiple myeloma

Abstract: Patients in complete clinical remission after myeloablative allogeneic stem cell transplantation (allo-SCT) were enrolled in a longitudinal study to assess the predictive value of molecular monitoring. Using polymerase chain reaction (PCR) for immunoglobulin gene rearrangements it was possible to generate a clonespecific molecular marker in 48 of 70 patients. Of these 48 patients, 16 (33%) attained durable PCR-negativity after transplantation, whereas 13 (27%) remained persistently PCR-positive and 19 (40%) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 24 publications
3
115
0
Order By: Relevance
“…Corradini et al demonstrated that a molecular remission achieved after myeloablative conditioning, as determined by polymerase chain reaction for immunoglobulin gene rearrangements generating a clone-specific molecular marker, was associated with possible cure, whereas patients with persistent minimal residual disease were destined to develop disease recurrence. 36 Similar results were seen in the RIC setting as well. 18 Patients who develop disease recurrence after SCT may respond to donor lymphocyte infusion (DLI).…”
Section: Discussionsupporting
confidence: 71%
“…Corradini et al demonstrated that a molecular remission achieved after myeloablative conditioning, as determined by polymerase chain reaction for immunoglobulin gene rearrangements generating a clone-specific molecular marker, was associated with possible cure, whereas patients with persistent minimal residual disease were destined to develop disease recurrence. 36 Similar results were seen in the RIC setting as well. 18 Patients who develop disease recurrence after SCT may respond to donor lymphocyte infusion (DLI).…”
Section: Discussionsupporting
confidence: 71%
“…84,85 This level has been achieved almost exclusively in the context of allogeneic stem cell transplantation in a very small subset of patients. However, in the near future, molecular remissions might be achieved in more patients with the combination of HDT and novel agents.…”
Section: Which Level Of Response Is Necessary?mentioning
confidence: 99%
“…Although the same has been shown in the setting of autologous transplantation, [32][33][34] the meaning of CR in the allogeneic transplantation setting is distinct since the ultimate goal is longterm cure. This is underlined by data showing the prognostic Allogeneic transplantation in multiple myeloma S Gerull et al significance of reaching molecular remission, 35,36 and suggests that molecular monitoring should be considered after allogeneic transplantation. The role of allogeneic transplantation in the era of novel agents has been a subject of growing debate.…”
Section: Discussionmentioning
confidence: 99%